The Management of Hajj Funds Optimization for the Pilgrims' Welfare Post-Covid-19 Pandemic - Permadi, Dedeng; Nasrulloh, Nasrulloh; Rahmawati, Alvi Ani Dwi; Widyaningrum, Resma (Journal of Islamic Economics Perspectives, 2022)
The pilgrimage in Indonesia has considerable economic potential. Its value always grows from year to year. Based on data from the Directorate General of Hajj and Umrah Organization, Indonesia received a quota of 221,000 hajj pilgrims in 2020. The quota is stated in the MoU (Memorandum of Understanding) between the Indonesian Minister of Religion and the Saudi Arabian Minister of Hajj and Umrah. With the MoU, it is hoped that Hajj funds can be controlled optimally so that these Hajj funds can be used to provide benefits for the welfare of Indonesian Hajj pilgrims during the pandemic. The research method used is a qualitative descriptive approach by referring to literature studies and previous research. Based on the results of the study, it can be concluded that with the establishment of the Hajj Financial Management Agency (BPKH), the financial management of the Hajj can be utilized to improve the facilities for organizing the Hajj and creating the welfare of the ummah through instruments from Islamic Financial Institutions, namely, Sukuk, State Sharia Securities (SBSN) and Time Deposits Sharia.